2006
DOI: 10.1086/507921
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Methicillin-ResistantStaphylococcus aureusDisseminated in a Home Care System

Abstract: MRSA colonization was common in the home care service analyzed. The fact that the majority of MRSA isolates obtained were primarily of nosocomial origin (and belonged to the so-called Brazilian epidemic clone) substantiated our findings that all but 1 patient had already been colonized before admission to the home care service. Only cross-transmission from patients to healthcare workers could be verified. On the basis of these results, we believe that a control program built on admission screening of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
(32 reference statements)
1
13
0
1
Order By: Relevance
“…Non multidrug-resistant MRSA isolates carrying SCC mec IV have already been identified in Brazilian hospitals, with patterns similar to USA100, USA300, USA400, USA800 and USA1100 clones,4, 13, 14, 22, 23 however, two isolates, in this study related to USA1100 and USA400, showed multidrug resistance profiles.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Non multidrug-resistant MRSA isolates carrying SCC mec IV have already been identified in Brazilian hospitals, with patterns similar to USA100, USA300, USA400, USA800 and USA1100 clones,4, 13, 14, 22, 23 however, two isolates, in this study related to USA1100 and USA400, showed multidrug resistance profiles.…”
supporting
confidence: 55%
“…The in vitro antimicrobial susceptibility to clindamycin and/or sulfamethoxazole/trimethoprim is a relevant characteristic described in strains with SCC mec IV 2 . The genotyping of Brazilian MRSA isolates allowed a better understanding of the dissemination patterns of the epidemic clones, such as, typically HA-MRSA and CA-MRSA 4 . The known virulence factor the exoprotein Panton-Valentine leucocidin (PVL) is traditionally seen in CA-MRSA, 5 however it has already been identified in methicillin-susceptible S. aureus and some rare HA-MRSA isolates 1, 6.…”
mentioning
confidence: 99%
“…USA800 isolates have been recently detected in hospitals located in Rio de Janeiro and Recife (10). This clone was also reported to colonize health workers of a home care service in Brazil (18). Although most SCCmecIV isolates are highly susceptible to non-β-lactams, in the present study two of the three USA800 isolates were resistant not only to β-lactam antibiotics, but also to erythromycin, clindamycin, tetracycline, and ciprofloxacin, a fact that may indicate a high ability of these SCCmecIV isolates to acquire multiple resistant genes.…”
mentioning
confidence: 87%
“…For example, a French study demonstrated that prior nursing home care was independently associated with infection by prevalent HA-MRSA strains when controlled for prior hospitalization, age of Ͼ65 years, and transfer from another institution (529), suggesting transmission from health care workers to patients in their homes. A Brazilian study demonstrated the transmission of MRSA from patients to their home-visiting health care workers (780). These data may not be applicable to an understanding of the transmission of CA-MRSA strains in households; if CA-MRSA is similarly transmitted from person to person by hand carriage, specific hand washing interventions may be appropriate to prevent its spread.…”
Section: Staphylococcus Aureus As a Commensal Organism: Role Of Asympmentioning
confidence: 99%